Teachers Perceptions’ of Differentiated Learning at SMKN 2 Tanjungpinang in English Subject - Fitri HZ, Natasya; Satria, Benni; Nopita, Dewi (Juliet, 2025)
The study aims to explore the perceptions of English teachers at SMKN 2 Tanjungpinang towards the implementation of differentiated learning in the context of Merdeka Curriculum. Using a qualitative approach, data was obtained through in-depth interviews and classroom observations. The results show that although teachers understand the concept of differentiated learning, they face various challenges in its implementation. The main obstacles include limited time, human resources and high workloads, so differentiated learning is considered difficult to implement optimally in heterogeneous classes. Teachers also highlighted that differentiated learning, while ideal for supporting students' learning needs, is not always relevant for English subjects that require a communicative approach. This study provides new insights into the importance of tailoring learning strategies to practical needs in the class, as well as underscoring the need for institutional support to ensure more effective implementation.